Isotopic (δ2H and δ13C) tracing the provenance and fate of individual fatty acids fueling migrating animals: A case study of the monarch butterfly (Danaus plexippus) - Pilecky, Matthias; Wassenaar, Leonard I.; Kainz, Martin J.; Anparasan, Libesha; Ramirez, M. Isabel; McNeil, Jeremy N.; Hobson, Keith A. (Frontiers in Ecology and Evolution, 2022)
Introduction Among long-distance migratory insects, the monarch butterfly (Danaus plexippus) is one of the most iconic, whose journey is fueled by nectar from flowering plants along the migratory route which may involve up to 3,500 km. Understanding how and where monarchs obtain their dietary resources to fuel migratory flight and ensure overwintering stores would provide new insights into the migratory strategy of this species and subsequently help focus conservation efforts. Methods This pilot study was designed as a first attempt to assess the composition, dynamics, and isotopic (δ2H, δ13C) composition of essential and non-essential fatty acids (FA) acquired or manufactured de novo from larval host milkweed (Asclepias spp.) by monarch butterflies and from adult emergence to overwintering. Results Data from controlled laboratory isotopic tracer tests suggested that adult monarchs convert their dietary energy mainly into 16:0 and 18:1 fatty acids and store them as neutral lipids in their abdomen. FA isotopic composition reflects not only dietary sources but also subsequent isotopic fractionation from metabolism. On the other hand, δ2H values of essential omega-3 fatty acid alpha-linolenic acid (ALA) correlated with δ2HWing, as markers of an individual’s geographic origin and indicated the importance of larval diet. Additionally, in wild-type females, high isotopic fractionation in δ13CALA between neutral and polar lipids might indicate increased bioconversion activity during gravidity. Finally, δ2HLIN showed positive H isotope fractionation from larval dietary sources, indicating that catabolic processes were involved in their manufacture. Furthermore, δ2HLIN showed a negative correlation with δ2HWing values, which could potentially be useful when investigating individual life-history traits, such as migratory catabolic efforts or periods of fasting. Discussion This interpretation was supported by significant larger variations in δ2HLIN and δ2HLIN overwintering monarchs compared to other FA. Altogether, our results provide the first evidence that the H isotopic analysis of individual fatty acids in migrating and overwintering monarchs can be used to infer the nutritional history of individuals including the provenance of nectaring sites used to fuel key life history events.